Using parasites as biological tag for Hilsa shad (Tenualosa ilisha) migration in Bangladesh waters (Bangladesh Journal of Zoology, 2021)
The study was aimed at following the movement of adolescent Tenualosa ilisha from nursery grounds to feeding and spawning grounds or other type of movements in Bangladesh waters. To accomplish this, data on metazoan endoparasites were used as biological tags for detection of migratory route. A total of 2667 host fishes were collected from eleven sites covering the three different ecological habitats of Bangladesh. Initial selection of parasites as biological tags was executed by using established criteria, primarily on the basis of different level of infection in different habitats. The role of incidental parasites as tags is also discussed. Overall fourteen species under eleven genus of endohelminths were identified from alimentary canal and associated organs of host, only three species of them had satisfied the criteria of being as biological tag. These are cestode parasite Ilisha parthenogenetica and acanthocephalan parasite Acanthosentis indica and Acanthosentis hilsai. Higher prevalence of these parasites at respective sites and the trend of prevalence of infection in size class of host fish demonstrated host‟s anadromous nature and reinforced the belief that the T. ilisha as a whole, migrates from the sea to the rivers via the estuaries and vice versa.Bangladesh J. Zool. 48(2): 243-251, 2020